Solar photovoltaic technology for small-scale irrigation in Ghana: suitability mapping and business models. Agricultural Water Management – Making a Business Case for Smallholders - Gebrezgabher, Solomie A.; Leh, Mansoor; Merrey, Douglas J.; Kodua, T.T.; Schmitter, Petra S. (International Water Management Institute, 2021)
This report assesses the potential of solar photovoltaic (PV) irrigation for smallholder agriculture in Ghana, using elements of business planning and business models with a suitability mapping approach. These approaches take into account the economic as well as environmental sustainability of expanding such technology. Using data from existing solar PV irrigation systems and interviews with key industry actors, the report discusses the regulatory and institutional context for investment in solar PV technology and outlines the technology supply chain, mapping the key actors and their roles. The financial viability of two empirical business cases – directly funding an agribusiness and subsidizing a cooperative model – is analyzed to assess the feasibility of expanding access to the technology. Furthermore, three solar PV irrigation business model scenarios are presented based on insights gained from the two empirical cases as well as from analyzing the existing policy and regulatory framework, the technology supply chain and environmental suitability. The potential for solar PV irrigation pumps is substantial, especially in northern Ghana, although care must be taken to avoid overpumping some aquifers. Achieving this potential will require strengthening the policy framework and making finance available at a reasonable cost. The report identifies alternative financing mechanisms and business models that have been tried elsewhere and can be adapted to Ghana, and makes recommendations to enhance the sustainable uptake of solar PV irrigation.